1560-1590 YILLARINDA OSMANLI DEVLETİNE KARŞI ARNAVUTİSYANLARININ SEBEPLERİ - (:unkn) unknown (My University, 2020)
0

This article analyzes the reasons why Albanians rebelled against the Ottoman Empire between 1560-1590 in the light of the new Ottoman Archive documents. Various claims exist on the underlying causes. One prominent claim explains that rebellion was due to the colonization of Albania by the Ottomans with some injustice practices such as high taxes and the oppression of opponents of the government. This such false claims were forced on many historians between 1945-1990 by the communist regime. Consequently, this kind of studies are far from revealing the true reasons of rebellion. When the documents of the Ottoman Archives have been examined, such claims were found wrong and biased. In fact, Albanians didn’t rebel for any political purpose, didn’t seek to resist oppression nor to establish their own independency. The core reason for the rebellions was that Albanians living in high and mountainous region and were not able to adapt to the taxes and laws imposed by the Ottomans. Keywords: History, Albania, Ottoman Empire, Rebellion, the Reasons
THE REASONS OF ALBANIAN REBELLIONS AGAINST OTTOMAN EMPIRE OCCURRED BETWEEN 1560-1590